Measuring the Returns to the GED : Using an Exogenous Change in GED Passing Standards as a Natural Experiment - Magnus Lofstrom; John Tyler (Institute for the Study of Labor (IZA), 2004)
In this paper, we exploit an exogenous change in the passing standard required to obtain a General Educational Development (GED) credential to identify the impact of the GED on the quarterly earnings of male dropouts, utilizing the Texas Schools Micro Data Panel (TSMP). These unique data contain demographic and GED test score information from the Texas Education Agency linked to pre- and post-test taking Unemployment Insurance quarterly wage records from the Texas Workforce Commission. Comparing Texas dropouts who acquired a GED before the passing standard was raised in 1997 to dropouts with the same test scores who failed the GED exams after the passing standard hike, we find no evidence of a positive ?GED effect? on earnings. The finding of no significant difference in pre-test taking earnings between the treatment and control group support the validity of the natural experiment. Our results are robust to a number of specifications and sub-samples of our general sample population of 16-40 year old males.
Keywords: J31; I2; 330; GED; returns to education; natural experiment; Bildungsabschluss; Bildungsertrag; Experiment; Schätzung; Vereinigte Staaten